Analysis of the SIRP epidemic model with anti-worm patching. Issue 2 (3rd April 2018) - Niranjan, Utkarsh; Agrawal, Ramesh Kumar; Lall, Brejesh
ABSTRACT: In this paper we analyse the effect of an anti-worm patching into a network inspired from human epidemiology. To achieve this we propose a new extended model of Susceptible–Infected–Recovered model. In which we introduced a new compartment, named as 'Patched'. This is a compartment where nodes/computers are not prone to worm attacks owing to an anti-worm patch being installed in them. We call our model Susceptible–Infected–Recovered–Patched model. We perform an exhaustive equilibrium analysis both analytically and numerically for the 'Worm' and 'Worm-free' scenarios. The model assumes that the anti-worm patch spreads like the worm does in the network. The equilibrium analysis illustrates how the population dynamics responds to different parameters involved in the model. We have also shown the effect of user vigilance in the model and observed that a more vigilant population of computer users is helpful to remove worm quickly from a network.